1962
DOI: 10.1902/jop.1962.33.3.209
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Periodontal Hazards of Third Molars

Abstract: T HE diagnosis and treatment of third molars often have been cited as being special problems to the oral surgeon and orthodontist, but the relationship of the third molars and their extraction to gingival changes, loss of bone, development of periodontal pockets, and exposure of the cementum on the distal of the second molars has received very little attention. Most of the studies of the status of the third molar have been directed towards classification of impactions, surgical procedures for their removal, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 2 publications
3
46
0
1
Order By: Relevance
“…These data on periodontal pathology related to retained third molars are the most extensive to date. Interestingly, these findings are also congruent with the classic observations of Ash et al (1962). Our study provides additional evidence for the association while also providing novel longitudinal data, with over 20+ years of follow-up, comparing second molar risk to situations where third molars are absent or unerupted.…”
Section: Discussionsupporting
confidence: 88%
“…These data on periodontal pathology related to retained third molars are the most extensive to date. Interestingly, these findings are also congruent with the classic observations of Ash et al (1962). Our study provides additional evidence for the association while also providing novel longitudinal data, with over 20+ years of follow-up, comparing second molar risk to situations where third molars are absent or unerupted.…”
Section: Discussionsupporting
confidence: 88%
“…Daniel Richardson and Thomas b. Dodson [8] studied the risk of periodontal defects after third molar surgery and found that 48% had worsening of their periodontal measures after third molar removal who had healthy periodontal status preoperatively. Other studies correlating to these findings are Ash et al [9], Chin quee et al [10], Osborne et al [11]. In contrast to this, there was improvement in periodontal conditions of second molar following the removal of third molar and were reported in studies by Pecora et al [12], Grondahl and Lekolm [13].…”
Section: Genesis Of Wisdom Teethmentioning
confidence: 79%
“…The radiographic techniques utilized were also different in those studies. Furthermore, they did not use the same methods of measurement and calibration, [18][19][20][21][22][23][24][25][26][27][28][29] nor did the majority of them evaluate the error of their radiographic technique. [19][20][21][22][23][24][25][26] Krausz et al 27 twice performed linear computerized measures of bone defects in panoramic radiographs, with minutes between them initially and 12 months later; the error between these evaluated measures was about 5% (r 2 5 95%).…”
Section: Discussionmentioning
confidence: 99%